Age-related trajectories of the development of social cognition - Yan, Zhi-Xiong; He, Zhe; Jiang, Ling-Hui; Zou, Xia (Frontiers in Psychology, 2024)
Age-related trajectories of intrinsic functional connectivity (iFC), the interconnections between discrete regions of the human brain, for processes related to social cognition (SC), provide neural imaging evidence for social development and can guide clinical interventions when such development is atypical. However, due to the lack of studies investigating brain development over a wide range of ages, the neural mechanisms of SC remain poorly understood, although considerable behavior-related evidence has been obtained. The present study mapped vortex-wise iFC features between SC networks and the entire cerebral cortex by using common functional networks, charting the corresponding age-related trajectories. Three networks (moral cognition, theory of mind [ToM], and empathy) were selected as representatives SC networks.The Nathan Kline Institute -Rockland Sample Enhanced (n = 316, ages 8-83 years old) dataset was employed to delineate iFC characteristics and construct trajectories from resting-state functional magnetic resonance imaging findings. The results revealed that the SC networks display unique and overlapping iFC profiles. The iFC of empathy network, an age-sensitive network, with dorsal attention network was found to exhibit a linear increasing pattern, that with the ventral attention network was discovered to exhibit a linear decreasing pattern, and that with the somatomotor and dorsal attention networks was found to exhibit a quadric-concave iFC pattern. Additionally, a sexspecific effect was observed for the empathy network, which exhibits linear and quadric sex-based differences in iFC with the frontoparietal and vision networks, respectively. The iFC of the ToM network with the ventral attention network exhibits a pronounced quadric-convex (inverted U-shape) trajectory. No linear or quadratic